FEELINGS OF FEAR IN WOMEN - Nodira KHUDOYNAZAROVA (Scholar Express Journal, 2023)
This article deals with the feeling of fear in women and its differences from representatives of other sexes, the nature of the origin of the feeling of fear and anxiety, the influence of the social roles performed by them - mother, wife, housewife, etc., on the development of fear in women . causes of constant fear and anxiety , manifestations of fear in women of different ages are highlighted. Also, constant fear and anxiety in life is often observed in women , the reason for this is that women are different from men , women deal with emotions rather than reason . and they are reported to be more subject to hormonal fluctuations .
Keywords: Woman; fear; object of fear; anxiety